PENGARUH PENGAPURAN DAN PEMUPUKAN FOSFOR PADA TANAH YANG SERING TERGENANG TERHADAP PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) - Bukhari Bukhari; Nuryulsen Safridar; Rudi Fadli (Jurnal Agroristek, 2020)
The purpose of this study were: (1) To determine the effect of dolomite lime and phosphorus fertilization on soils that were often inundated on the growth and yield of peanuts, (2) to determine the interaction between these two factors on the growth and production of peanuts in soils that were often inundated. The experimental design used in this study was "Randomized Block Design", with 3 (three) replications and 2 (two) factors studied, namely the effect of dolomite (Liming) (K) lime with 4 (four) levels, namely; K0 = 0 gr / polybag, K1 = 2 gr / polybag, K2 = 4 gr / polybag, and K3 = 6 gr / polybag. While Phosphorus (Sp-36) (P) fertilization with 3 (three) levels, namely; P0 = 0 gr / polybag, P1 = 2.5 gr / polybag, P2 = 5 gr / polybag. The variables observed to show the effect of dolomite lime and Sp-36 fertilization were: (1) Plant height: measured at the age of 21, 42, 63 days after planting (DAS). (2) A number of branches per clump (cm). (3) The number of flowers per family. (4) The yield of pods per polybag (gram). And (5) the number of pods per (fruit). The results of the research on the effect of dolomite liming treatment on the growth and yield of groundnut showed that: (1) had a very significant effect (level of 1%) on plant height at 21, 42 and 63 DAS, (2) had no significant effect on the number of branches per clump, (2) 3) It had a significant effect (level of 5%) on the number of flowers per clump, (4) had a very significant effect (level of 1%) on the yield of pods per polybag, and (5) had a very significant effect (level of 1%) on the number of pods per hill. While the effect of phosphorus fertilization treatment on the growth and yield of peanuts showed that: (1) had a very significant effect (level of 1%) on plant height at 21 and 42 DAS, (2) had no significant effect on the number of branches per clump, (3) very real (level 1%) on the number of flowers per clump, (4) had a very significant effect (level 1%) on the yield of pods per polybag, and (5) had a significant effect (level 5%) on the number of pods per hill. The interaction between dolomite liming and phosphorus fertilization on the growth and yield of peanuts in all the variables studied (plant height, number of branches per clump, number of flowers per clump, a yield of pods per polybag and number of pods per hill), showed a very significant effect (level 1%).Keywords: Dolomite lime, phosphorus fertilization, soil, peanuts.